The Effect of Animated Video in Stimulating Sexual Understanding of 5-6 Years Old Children in Gowa Regency - Anita Anita; Syamsuardi Saodi; Sitti Nurhidayah Ilyas; Rika Kurnia R.; Andi Ibrahim (Universitas Muhammadiyah Enrekang, 2023)
understanding of children aged 5-6 years in kindergarten in Gowa Regency. This study used purposive sampling method with a sample of 60 children. 30 children from Nurul Fadhilah Kindergarten as the experimental group and 30 children from Pertiwi Tamarunang Kindergarten as the control group. The data analysis method in this research is prerequisite test and independent sample t-test. From the results of the t-test based on the assumption of equal variance, there is a difference in the level of sexual understanding of 5 to 6 year olds in the experimental group that is treated and the control group and not treated. The research hypothesis states that there is an effect of animated videos in stimulating the sexual understanding of children aged 6 to 6 years in kindergarten in Gowa Regency which can be proven from the results of the independent sample t-test. If there is a difference in the average sexual understanding of children in Nurul Fadhilah Kindergarten and Pertiwi Tamarunang Kindergarten, then H0 is rejected and H1 is accepted.